ANENCEPHALY MEDICAL INDICATION AS TO INTERRUPT PREGNANCY SUPPORT BIBLIOGRAPHICAL - Távara Orosco, Luis (2015)
OBJECTIVE: To identify thesis that contribute to support or disclaim pregnancy interruption in cases of anencephaly. MATERIALS AND METHODS: Search of current internet literature, available magnetic media or edited documents. Anencephaly frequency, related factors, repercussions on the mother, fetus and newborn associated problems, prevention, and both ethical and legal arguments were reviewed. RESULTS: Anencephaly has variable frequency; its origin in based on both genetic and environment factors. There are repercussions on mother‘s physical and mental health and fetal and newborn organs and systems. These considerations avail anencephaly as a medical, ethical and legal indication for pregnancy interruption. CONCLUSION: Anencephaly justifies pregnancy interruption when requested by the mother.